Organic-inorganic hybrid fluoride-free anti-fingerprint transparent coating as well as preparation method and application thereof
Through the combination of organic-inorganic hybrid silicone resin and tung oil derivatives, a fluorine-free anti-fingerprint transparent coating is prepared by spray coating and ultraviolet curing technology, which solves the shortcomings of the existing coating in terms of wear resistance, fingerprint resistance and transmittance, and achieves an efficient, environmentally friendly and durable coating effect.
Patent Information
- Application Number
- CN202411988087.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The existing hydrophobic coatings have shortcomings in wear resistance, fingerprint resistance and transmittance, especially the coatings formed on the surface are not wear-resistant, have poor stability, and use fluorine-containing compounds with high toxicity.
Fluorine-free anti-fingerprint transparent coating was prepared by spraying and ultraviolet curing techniques using a combination of organic-inorganic hybrid silicone resin, tung oil derivatives, photoinitiators and organic solvents. The coating achieves good hydrophobic properties, wear resistance and fingerprint resistance by introducing flexible and hydrophobic tung oil combined with high hardness silicone.
It realizes a fluorine-free, transparent and wear-resistant coating, with high hardness, low surface energy and good hydrophobic properties, can quickly cure, high production efficiency, and is environmentally friendly and non-toxic.
Smart Images

Figure BDA0005223044110000091 
Figure BDA0005223044110000093 
Figure BDA0005223044110000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of anti-fingerprint and wear-resistant coating materials, and in particular to an organic-inorganic hybrid fluorine-free anti-fingerprint transparent coating and a preparation method and application thereof. Background Art
[0002] Advanced multifunctional coatings have a wide range of applications in electronic displays, automotive windshields, automotive interiors, and other fields. For example, the touch screen of a foldable smartphone or tablet requires a transparent, hard, and flexible coating to protect it from external mechanical scratches, impacts, and bending. In addition, anti-fingerprint and anti-smudge properties are also very important in daily use, so a fully hydrophobic coating with oleophobic and hydrophobic functions is preferred. However, due to the inherent conflict between high hardness, high flexibility, and fully hydrophobic properties, it is a huge challenge to meet the above requirements at the same time. At the same time, for fully hydrophobic coatings, their surfaces need to be carefully customized to form nano- and micro-scale surface features or to form special voids, but these methods easily lead to low transparency and poor scratch resistance.
[0003] In order to solve these contradictions, the development of organic-inorganic hybrid coatings is an effective way. Specifically, silane-derived silicon-based materials are the basis of such coatings, because siloxane can form an inorganic Si-O core, providing glass-like hardness, while other organic groups can give the coating flexibility and the required functionality. Acrylic monomers and oligomers, as a commonly used UV-curable reactive diluent, have been widely used in UV coatings or formulations. However, most acrylic monomers or oligomers (such as hydroxyethyl acrylate, diethylene glycol diacrylate, trimethylpropyl triacrylate, pentaerythritol triacrylate, etc.) have the disadvantages of high volatility, skin irritation, and poor odor, which greatly limits the application range of these materials. Combining acrylic reactive monomers with other organic substances to form new UV-curable reactive monomers can effectively overcome the above shortcomings. For example, combining tung oil with acrylate reactive monomers can prepare low-volatility, low-viscosity, and highly reactive UV-curable reactive monomers, which is a good choice and can well meet the requirements of industrial applications.
[0004] For example, patent CN113372803A discloses an anti-corrosion, anti-icing, self-cleaning, super-hydrophobic coating and its preparation method and application. The invention adopts 1H, 1H, 2H, 2H-perfluorodecyl trimethoxysilane to coat SiO 2 Hydrophobic modification is performed to reduce its surface energy, and then modified SiO 2Doped polyester thermoplastic polyurethane elastomer is used to prepare an anticorrosive self-cleaning super hydrophobic coating with good hydrophobic properties. Applying it on the surface of metal equipment can effectively improve the hydrophobicity of the surface of the metal equipment and improve its anti-icing performance. The disadvantage of this patent is that the coating formed on the surface is not wear-resistant, has poor stability, and uses toxic fluorinated compounds in the preparation process. Patent CN106146754A introduces a preparation method and application of a silicon-containing nanogel photocurable resin for 3D printing, prepares and mixes a silicone resin prepolymer with an acryloyloxy group, a acryloyloxy-modified white carbon black as a reinforcing filler, a photoinitiator, etc. to prepare a photocurable silicone resin prepolymer, and a 3D printing ultraviolet light-cured transparent silicone resin composite material can be obtained by photopolymerization, which has good ultraviolet radiation resistance, thermal stability, weather resistance, electrical insulation, hydrophobicity and flame retardancy. However, a large amount of solvent needs to be used in this preparation process, and it contains a large amount of powder, which is not environmentally friendly. Patent CN104530852A discloses the preparation of a highly hydrophobic fluorocarbon coating for a photovoltaic module backplane, providing a simple preparation process, nano-silicon dioxide is uniformly dispersed in the main resin after being hydrophobically modified by a coupling agent, and a micro-nano rough texture structure is formed after being coated on a substrate, and the low surface energy of the fluorocarbon resin itself is combined to make its surface have a high hydrophobicity of the "lotus effect", while avoiding the adhesion of dew, rain and water vapor on the surface of the backplane, improving the hydrolysis resistance of the backplane, and having a good antifouling effect. However, the patent uses hydrophobic particles to mix with fluorocarbon resin, and the mixing difficulty is large, and the uniformity of the coating is difficult to be guaranteed, which has an adverse effect on light transmission performance and mechanical properties. And using fluorocarbon resin as the main resin contains a large amount of fluorine elements, which is not conducive to environmental protection and has high cost. The above-mentioned hydrophobic coating introduces toxic fluorine-containing groups or adds a large amount of powder to achieve a hydrophobic effect, which will reduce the stability, wear resistance and transmittance of the coating. In view of the problems existing in the current technology, a fluorine-free, transparent and hydrophobic and wear-resistant coating is urgently needed to be developed. Summary of the invention
[0005] The object of the present invention is to provide an organic-inorganic hybrid fluorine-free anti-fingerprint transparent coating and a preparation method and application thereof, so as to solve the technical problems of the existing hydrophobic coating in terms of wear resistance, anti-fingerprint performance and low transmittance.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a method for preparing an organic-inorganic hybrid fluorine-free anti-fingerprint transparent coating, comprising the following steps:
[0008] 1) mixing an organic-inorganic hybrid silicone resin, a tung oil derivative, a photoinitiator and an organic solvent to obtain a mixed coating;
[0009] 2) The mixed coating is coated on a substrate and cured by ultraviolet light to obtain an organic-inorganic hybrid fluorine-free anti-fingerprint transparent coating.
[0010] Furthermore, the preparation method of the organic-inorganic hybrid silicone resin comprises the following steps:
[0011] Mixing siloxane, tetraethyl silicate and a silane coupling agent in an acidic solvent for hydrolysis to obtain an organic-inorganic hybrid silicone resin;
[0012] The molar ratio of the siloxane, tetraethyl silicate and silane coupling agent is 1:0.2-9:0.2-9.
[0013] Further, the siloxane comprises one or more of trimethylchlorosiloxane, tetramethyldivinyldisiloxane, vinylpentamethyldisiloxane, trimethylmethoxysilane, trimethylethoxysilane, hexamethyldisiloxane, dimethyldimethoxysilane and dimethyldiethoxysilane;
[0014] The silane coupling agent comprises one or more of γ-methacryloxypropyl trimethoxysilane, γ-methacryloxypropyl triethoxysilane, γ-mercaptopropyl trimethoxysilane, γ-mercaptopropyl triethoxysilane, γ-glycidyloxypropyl trimethoxysilane, γ-glycidyloxypropyl triethoxysilane, γ-aminopropyl triethoxysilane, γ-aminopropyl trimethoxysilane, vinyl trimethoxysilane, vinyl triethoxysilane, phenyl trimethoxysilane, phenyl triethoxysilane, dodecyl trimethoxysilane, dodecyl triethoxysilane, hexadecyl trimethoxysilane, hexadecyl triethoxysilane, methyl triethoxysilane and methyl trimethoxysilane;
[0015] The acid in the acidic solvent comprises one or more of toluenesulfonic acid, oxalic acid, hydrochloric acid and acetic acid; the solvent in the acidic solvent comprises at least two of toluene, methanol, ethanol, ethylene glycol, glycerol, ethylene glycol methyl ether, ethylene glycol butyl ether, propylene glycol methyl ether, chloroform, tetrahydrofuran, butyl acetate, dimethyl sulfoxide, isopropanol and water, and the amount of the acidic solvent is 10-60% of the total mass of siloxane, tetraethyl silicate and silane coupling agent.
[0016] Furthermore, the hydrolysis temperature is 25 to 90° C., and the hydrolysis time is 6 to 24 hours.
[0017] Furthermore, the preparation method of the tung oil derivative comprises the following steps:
[0018] Tung oil anhydride, acrylate monomer and polymerization inhibitor are mixed, and reacted under heating and the action of a catalyst to obtain a tung oil derivative;
[0019] The molar ratio of tung oil anhydride to acrylate monomer is 1:5-7, the content of the inhibitor is 0.5-5% of the total mass of tung oil anhydride and acrylate monomer, and the mass of the catalyst is 0.1-2% of the total mass of tung oil anhydride and acrylate monomer;
[0020] The mass of the tung oil derivative is 1-50% of the total mass of the organic-inorganic hybrid silicone resin and the tung oil derivative.
[0021] Further, the acrylate monomer comprises one or more of hydroxyethyl methacrylate, 2-hydroxyethyl acrylate, glycidyl methacrylate, 2-ethoxyethyl acrylate, 2-cyanoacrylate, β-hydroxypropyl acrylate, β-hydroxypropyl methacrylate, dipentaerythritol pentaacrylate and pentaerythritol triacrylate; the polymerization inhibitor comprises one or more of hydroquinone, p-hydroxyanisole and methylhydroquinone; the catalyst comprises p-toluenesulfonic acid and / or N,N-dimethylethanolamine;
[0022] The reaction temperature is 60-100° C., and the reaction time is 4-12 hours.
[0023] Furthermore, the photoinitiator comprises one or more of photoinitiator 250, photoinitiator 6992, photoinitiator BDK, photoinitiator 369, photoinitiator MBF, photoinitiator PBZ, photoinitiator EDB, photoinitiator 379, photoinitiator 784, photoinitiator 2959, photoinitiator 184-L, photoinitiator TPO, photoinitiator TPO-L and photoinitiator 1173; the mass of the photoinitiator is 1 to 5% of the total mass of the organic-inorganic hybrid silicone resin and the tung oil derivative.
[0024] Furthermore, the organic solvent comprises one or more of acetone, tetrahydrofuran, ethanol, methanol, ethyl acetate, n-butyl acetate, chloroform, dichloromethane, dimethyl sulfoxide, propylene glycol methyl ether, ethylene glycol butyl ether, n-pentane and toluene; and the mass of the organic solvent is 1 to 10 times the total mass of the organic-inorganic hybrid silicone resin and the tung oil derivative.
[0025] The invention provides an organic-inorganic hybrid fluorine-free anti-fingerprint transparent coating.
[0026] The present invention also provides an application of an organic-inorganic hybrid fluorine-free anti-fingerprint transparent coating in an anti-fingerprint self-cleaning wear-resistant material.
[0027] Beneficial effects of the present invention:
[0028] The present invention provides a tung oil derivative modified fluorine-free anti-fingerprint wear-resistant transparent coating, which is prepared into a solution by a tung oil derivative, an organic-inorganic hybrid silicone resin, a photoinitiator and an organic solvent, and is sprayed onto a substrate by a spray gun, and is cured by ultraviolet light to form a film. The organic-inorganic hybrid silicone resin itself has high hardness and transparency, and low surface energy, but the pure silicone resin coating is easy to crack, and it is necessary to introduce a flexible segment into the silicone resin. Therefore, we introduce flexible and hydrophobic tung oil, so that the film does not crack and has good hydrophobicity, wear resistance and anti-fingerprint performance.
[0029] The present invention uses organic-inorganic hybrid silicone resin, and introduces tetraethyl silicate while synthesizing an organic silicone resin with a high degree of intramolecular crosslinking. Since tetraethyl silicate has a small steric hindrance, it can self-condense faster to form a "hard core", providing the silicone resin with strength similar to quartz, while the silane coupling agent and siloxane form a branched structure, so the silicone resin as a whole presents a cross-linked molecular structure in which spherical and branched segments coexist, and this structure can make the material have a higher hardness. At the same time, the low surface energy of the silicone resin itself makes the material have better hydrophobic properties, and it is fluorine-free, low-toxic and pollution-free, making the material more environmentally friendly.
[0030] The coating of the present invention uses tung oil as a raw material, which has the characteristics of low cost, low toxicity, and renewable biological resources. Tung oil can be extracted from tung oil tree seeds, and the monomer source is wide. At the same time, the preparation method used is simple, and ultraviolet light curing is used, making the preparation process more green and environmentally friendly. DETAILED DESCRIPTION
[0031] The present invention provides a method for preparing an organic-inorganic hybrid fluorine-free anti-fingerprint transparent coating, comprising the following steps:
[0032] 1) mixing an organic-inorganic hybrid silicone resin, a tung oil derivative, a photoinitiator and an organic solvent to obtain a mixed coating;
[0033] 2) The mixed coating is coated on a substrate and cured by ultraviolet light to obtain an organic-inorganic hybrid fluorine-free anti-fingerprint transparent coating.
[0034] In the present invention, the preparation method of the organic-inorganic hybrid silicone resin comprises the following steps:
[0035] Mixing siloxane, tetraethyl silicate and a silane coupling agent in an acidic solvent for hydrolysis to obtain an organic-inorganic hybrid silicone resin;
[0036] The molar ratio of the siloxane, tetraethyl silicate and silane coupling agent is 1:0.2-9:0.2-9, preferably 1:1-8:1-8, more preferably 1:1.5-6:1.5-5, and more preferably 1:1.6:2.3.
[0037] In the present invention, it is preferred that the silane coupling agent and siloxane are first prepared into a solution, and then tetraethyl silicate is added to obtain the organic-inorganic hybrid silicone resin.
[0038] In the present invention, the siloxane is preferably one or more of trimethylchlorosiloxane, tetramethyldivinyldisiloxane, vinylpentamethyldisiloxane, trimethylmethoxysilane, trimethylethoxysilane, hexamethyldisiloxane, dimethyldimethoxysilane and dimethyldiethoxysilane;
[0039] The silane coupling agent is preferably one or more of γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropyltriethoxysilane, γ-mercaptopropyltrimethoxysilane, γ-mercaptopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, γ-glycidyloxypropyltriethoxysilane, γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, dodecyltrimethoxysilane, dodecyltriethoxysilane, hexadecyltrimethoxysilane, hexadecyltriethoxysilane, methyltriethoxysilane and methyltrimethoxysilane; when the silane coupling agent is the above two types, the present invention has no special provisions on the ratio of different types of silane coupling agents, which can be adjusted according to actual needs.
[0040] The acid in the acidic solvent is preferably one or more of toluenesulfonic acid, oxalic acid, hydrochloric acid and acetic acid; when the acid is the above two types, the present invention has no special provisions on the ratio of different types of acids, which can be adjusted according to actual needs.
[0041] In the present invention, the solvent in the acidic solvent is preferably at least two of toluene, methanol, ethanol, ethylene glycol, glycerol, ethylene glycol methyl ether, ethylene glycol butyl ether, propylene glycol methyl ether, chloroform, tetrahydrofuran, butyl acetate, dimethyl sulfoxide, isopropanol and water, preferably a mixed solvent formed by mixing one of toluene, methanol, ethanol, ethylene glycol, glycerol, ethylene glycol methyl ether, ethylene glycol butyl ether, propylene glycol methyl ether, chloroform, tetrahydrofuran, butyl acetate, dimethyl sulfoxide, isopropanol and water, more preferably a mixed solvent of ethanol and water, and the molar ratio of ethanol to water is 1:2.
[0042] In the present invention, the amount of the acidic solvent is 10-60% of the total mass of siloxane, tetraethyl silicate and silane coupling agent, preferably 35-50%, more preferably 40-45%.
[0043] In the present invention, the hydrolysis is carried out under stirring, and the stirring speed is 500-1000rpm, preferably 800rpm; the hydrolysis temperature is 25-90°C, preferably 30-80°C, and more preferably 40-60°C; the hydrolysis time is 6-24h, preferably 6-12h, and more preferably 8-10h.
[0044] In the present invention, the preparation method of the tung oil derivative comprises the following steps:
[0045] Tung oil anhydride, acrylate monomer and polymerization inhibitor are mixed, and reacted under heating and the action of a catalyst to obtain a tung oil derivative;
[0046] The molar ratio of tung oil anhydride to acrylate monomer is 1:5-7, preferably 1:6; the content of the polymerization inhibitor is 0.5-5% of the total mass of tung oil anhydride and acrylate monomer, preferably 1-3%, more preferably 2%; the mass of the catalyst is 0.1-2% of the total mass of tung oil anhydride and acrylate monomer, preferably 0.5-1%, more preferably 0.8%;
[0047] The mass of the tung oil derivative is 1 to 50% of the total mass of the organic-inorganic hybrid silicone resin and the tung oil derivative, preferably 10 to 40%, and more preferably 20 to 30%.
[0048] In the present invention, the acrylate monomer is preferably one or more of hydroxyethyl methacrylate, 2-hydroxyethyl acrylate, glycidyl methacrylate, 2-ethoxyethyl acrylate, 2-cyanoacrylate, β-hydroxypropyl acrylate, β-hydroxypropyl methacrylate, dipentaerythritol pentaacrylate and pentaerythritol triacrylate; the inhibitor is preferably one or more of hydroquinone, p-hydroxyanisole and methylhydroquinone; the catalyst is preferably p-toluenesulfonic acid and / or N,N-dimethylethanolamine.
[0049] In the present invention, the reaction is carried out under stirring, the stirring speed is 200-500 rpm, preferably 400 rpm, the reaction temperature is 60-100°C, preferably 70-90°C, and more preferably 75-85°C; the reaction time is 4-12h, preferably 4-10h, more preferably 5-9h, and more preferably 6-8h.
[0050] In the present invention, the photoinitiator is preferably one or more of photoinitiator 250, photoinitiator 6992, photoinitiator BDK, photoinitiator 369, photoinitiator MBF, photoinitiator PBZ, photoinitiator EDB, photoinitiator 379, photoinitiator 784, photoinitiator 2959, photoinitiator 184-L, photoinitiator TPO, photoinitiator TPO-L and photoinitiator 1173; the mass of the photoinitiator is 1 to 5% of the total mass of the organic-inorganic hybrid silicone resin and the tung oil derivative, preferably 1.4 to 4%, and further preferably 1.5 to 2.5%.
[0051] In the present invention, the organic solvent is preferably one or more of acetone, tetrahydrofuran, ethanol, methanol, ethyl acetate, n-butyl acetate, chloroform, dichloromethane, dimethyl sulfoxide, propylene glycol methyl ether, ethylene glycol butyl ether, n-pentane and toluene; the mass of the organic solvent is 1 to 10 times the total mass of the organic-inorganic hybrid silicone resin and the tung oil derivative, preferably 1.5 to 5 times, and more preferably 2 to 3 times.
[0052] In the present invention, there is no particular limitation on the substrate. The present invention can form a film on the surface of any well-known coating substrate (plastic, glass, composite material, film, metal). In the embodiments of the present invention, the substrate used is a glass slide.
[0053] The invention adopts a spraying or scraping method to coat the mixed coating on the surface of the substrate, and then performs ultraviolet light curing to obtain an organic-inorganic hybrid fluorine-free anti-fingerprint transparent coating.
[0054] In the present invention, in the spraying method, the spraying pressure is preferably 0.1 to 3 MPa, more preferably 0.2 to 2 MPa, and further preferably 0.25 to 0.3 MPa. In the present invention, the coating amount of the mixed coating on the substrate is preferably 0.001 to 0.005 g / cm 3 .
[0055] In the present invention, the ultraviolet light curing is preferably carried out under a UV-LED lamp, and the ultraviolet light curing time is preferably 30 to 900 s, more preferably 60 to 300 s, and further preferably 60 to 150 s.
[0056] During the UV curing process, the photoinitiator absorbs UV light and converts into free radicals, which trigger cross-linking of active groups in the silicone resin, thereby curing the coating.
[0057] The invention provides an organic-inorganic hybrid fluorine-free anti-fingerprint transparent coating.
[0058] The present invention also provides an application of an organic-inorganic hybrid fluorine-free anti-fingerprint transparent coating in an anti-fingerprint self-cleaning wear-resistant material.
[0059] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0060] Example 1
[0061] (1) Place the glass slide in water and use an ultrasonic cleaner to sonicate for 15 minutes, then place the substrate in ethanol and use an ultrasonic cleaner to sonicate for 15 minutes to obtain a substrate with a clean surface.
[0062] (2) adding 1 g of tung oil derivative, 0.4 g of photoinitiator 184-L, and 20 g of ethanol to 9 g of organic-inorganic hybrid silicone resin, and stirring evenly to obtain a mixed coating;
[0063] (3) spraying the mixed coating onto a cleaned glass slide at a pressure of 0.25 MPa;
[0064] (4) The glass slide sprayed with the mixed coating was placed under a UV-LED lamp and irradiated with ultraviolet light for 90 seconds to obtain a transparent coating.
[0065] The preparation process of the organic-inorganic hybrid silicone resin comprises the following steps:
[0066] In a single-mouth round-bottom flask, first add 6.00g ethanol and 4.68g deionized water, then add 0.25g acetic acid, 1.81g dimethyldimethoxysilane, 16.38g γ-methacryloxypropyltrimethoxysilane, 10.24g tetraethyl silicate, stir with magnetic stirring at 800rpm, and react at 40℃ for 6h. The structure of the obtained organic-inorganic hybrid silicone resin is as follows:
[0067]
[0068] Among them, R is or CH 3 ;
[0069] The preparation process of tung oil derivatives comprises the following steps:
[0070] Under nitrogen protection, tung oil anhydride and N, N-dimethylethanolamine accounting for 1% of the total mass of the system were added to a three-necked flask, mechanically stirred at 400rpm and heated. When the temperature rose to 70°C, hydroxyethyl methacrylate and hydroxyethyl methacrylate with a molar amount of 6 times that of tung oil anhydride, as well as 1% of the total mass of p-hydroxyanisole were added dropwise. The temperature was raised to 100°C and reacted for 6 hours. The structure of the obtained tung oil derivative T6 is as follows:
[0071]
[0072] Example 2
[0073] (1) Place the glass slide in water and use an ultrasonic cleaner to sonicate for 15 minutes, then place the substrate in ethanol and use an ultrasonic cleaner to sonicate for 15 minutes to obtain a substrate with a clean surface.
[0074] (2) adding 1 g of tung oil derivative, 0.4 g of photoinitiator 184-L, and 20 g of ethanol to 9 g of organic-inorganic hybrid silicone resin, and stirring evenly to obtain a mixed coating;
[0075] (3) spraying the mixed coating onto a cleaned glass slide at a pressure of 0.25 MPa;
[0076] (4) The glass slide sprayed with the mixed coating was placed under a UV-LED lamp and irradiated with ultraviolet light for 90 seconds to obtain a transparent coating.
[0077] The preparation process of the organic-inorganic hybrid silicone resin comprises the following steps:
[0078] In a single-mouth round-bottom flask, first add 6.00g ethanol and 4.68g deionized water, then add 0.15g hydrochloric acid, 3.24g trimethylchlorosilane, 16.38g γ-methacryloxypropyltrimethoxysilane and 10.24g tetraethyl silicate, stir with magnetic force at 800rpm, and react at 40℃ for 6h. The structure of the obtained organic-inorganic hybrid silicone resin is as follows:
[0079]
[0080] Among them, R is or CH 3 ;
[0081] The preparation process of tung oil derivatives comprises the following steps:
[0082] Under nitrogen protection, tung oil anhydride and N, N-dimethylethanolamine accounting for 1% of the total mass of the system were added to a three-necked flask, mechanically stirred at 400rpm and heated. When the temperature rose to 70°C, hydroxyethyl methacrylate and hydroxyethyl methacrylate with a molar amount of 6 times that of tung oil anhydride, as well as 1% of the total mass of p-hydroxyanisole were added dropwise. The temperature was raised to 100°C and reacted for 6 hours. The structure of the obtained tung oil derivative T6 is as follows:
[0083]
[0084] Example 3
[0085] (1) Place the glass slide in water and use an ultrasonic cleaner to sonicate for 15 minutes, then place the substrate in ethanol and use an ultrasonic cleaner to sonicate for 15 minutes to obtain a substrate with a clean surface.
[0086] (2) adding 1 g of tung oil derivative, 0.4 g of photoinitiator 184-L, and 20 g of ethanol to 9 g of organic-inorganic hybrid silicone resin, and stirring evenly to obtain a mixed coating, wherein the tung oil derivative is the tung oil derivative in Example 1;
[0087] (3) spraying the mixed coating onto a cleaned glass slide at a pressure of 0.25 MPa;
[0088] (4) The glass slide sprayed with the mixed coating was placed under a UV-LED lamp and irradiated with ultraviolet light for 90 seconds to obtain a transparent coating.
[0089] The preparation process of the organic-inorganic hybrid silicone resin comprises the following steps:
[0090] In a single-mouth round-bottom flask, first add 6.00g ethanol and 4.68g deionized water, then add 0.25g acetic acid, 2.44g hexamethyldisiloxane, 16.38g γ-methacryloxypropyltrimethoxysilane, 1.73g hexadecyltrimethoxysilane and 10.24g tetraethyl silicate, stir with magnetic stirring at 800rpm, and react at 40℃ for 6h. The structure of the obtained organic-inorganic hybrid silicone resin is as follows:
[0091]
[0092] Among them, R is or CH 3 ;
[0093] Example 4
[0094] (1) Place the glass slide in water and use an ultrasonic cleaner to sonicate for 15 minutes, then place the substrate in ethanol and use an ultrasonic cleaner to sonicate for 15 minutes to obtain a substrate with a clean surface.
[0095] (2) adding 1 g of tung oil derivative, 0.4 g of photoinitiator 184-L, and 20 g of ethanol to 9 g of organic-inorganic hybrid silicone resin, and stirring evenly to obtain a mixed coating, wherein the tung oil derivative is the tung oil derivative in Example 1;
[0096] (3) spraying the mixed coating onto a cleaned glass slide at a pressure of 0.25 MPa;
[0097] (4) The glass slide sprayed with the mixed coating was placed under a UV-LED lamp and irradiated with ultraviolet light for 90 seconds to obtain a transparent coating.
[0098] The preparation process of the organic-inorganic hybrid silicone resin comprises the following steps:
[0099] In a single-mouth round-bottom flask, first add 6.00g ethanol and 4.68g deionized water, then add 0.15g hydrochloric acid, 3.24g trimethylchlorosilane, 16.38g γ-methacryloxypropyltrimethoxysilane, 1.73g hexadecyltrimethoxysilane and 10.24g tetraethyl silicate, stir with magnetic stirring at 800rpm, and react at 40℃ for 6h. The structure of the obtained organic-inorganic hybrid silicone resin is as follows:
[0100]
[0101] Among them, R is or CH 3 ;
[0102] Example 5
[0103] (1) Place the glass slide in water and use an ultrasonic cleaner to sonicate for 15 minutes, then place the substrate in ethanol and use an ultrasonic cleaner to sonicate for 15 minutes to obtain a substrate with a clean surface.
[0104] (2) adding 2 g of tung oil derivative, 0.4 g of photoinitiator 184-L, and 20 g of ethanol to 8 g of organic-inorganic hybrid silicone resin, and stirring evenly to obtain a mixed coating, wherein the organic-inorganic hybrid silicone resin is the organic-inorganic hybrid silicone resin in Example 3, and the tung oil derivative is the tung oil derivative in Example 1;
[0105] (3) spraying the mixed coating onto a cleaned glass slide at a pressure of 0.25 MPa;
[0106] (4) The glass slide sprayed with the mixed coating was placed under a UV-LED lamp and irradiated with ultraviolet light for 90 seconds to obtain a transparent coating.
[0107] Example 6
[0108] (1) Place the glass slide in water and use an ultrasonic cleaner to sonicate for 15 minutes, then place the substrate in ethanol and use an ultrasonic cleaner to sonicate for 15 minutes to obtain a substrate with a clean surface.
[0109] (2) adding 3 g of tung oil derivative, 0.4 g of photoinitiator 184-L, and 20 g of ethanol to 7 g of organic-inorganic hybrid silicone resin, and stirring evenly to obtain a mixed coating, wherein the organic-inorganic hybrid silicone resin is the organic-inorganic hybrid silicone resin in Example 3, and the tung oil derivative is the tung oil derivative in Example 1;
[0110] (3) spraying the mixed coating onto a cleaned glass slide at a pressure of 0.25 MPa;
[0111] (4) The glass slide sprayed with the mixed coating was placed under a UV-LED lamp and irradiated with ultraviolet light for 90 seconds to obtain a transparent coating.
[0112] Comparative Example 1
[0113] (1) Place the glass slide in water and use an ultrasonic cleaner to sonicate for 15 minutes, then place the substrate in ethanol and use an ultrasonic cleaner to sonicate for 15 minutes to obtain a substrate with a clean surface.
[0114] (2) Add 0.4 g of photoinitiator 184-L and 20 g of ethanol to 10 g of organic-inorganic hybrid silicone resin, and stir evenly to obtain a mixed coating, wherein the organic-inorganic hybrid silicone resin is the silicone resin in Example 1.
[0115] (3) spraying the mixed coating onto a cleaned glass slide at a pressure of 0.25 MPa;
[0116] (4) The glass slide sprayed with the mixed coating was placed under a UV-LED lamp and irradiated with ultraviolet light for 90 seconds to obtain a transparent coating.
[0117] Comparative Example 2
[0118] (1) Place the glass slide in water and use an ultrasonic cleaner to sonicate for 15 minutes, then place the substrate in ethanol and use an ultrasonic cleaner to sonicate for 15 minutes to obtain a substrate with a clean surface.
[0119] (2) Add 0.4 g of photoinitiator 184-L and 20 g of ethanol to 10 g of organic-inorganic hybrid silicone resin, and stir evenly to obtain a mixed coating, wherein the organic-inorganic hybrid silicone resin is the silicone resin in Example 2.
[0120] (3) spraying the mixed coating onto a cleaned glass slide at a pressure of 0.25 MPa;
[0121] (4) The glass slide sprayed with the mixed coating was placed under a UV-LED lamp and irradiated with ultraviolet light for 90 seconds to obtain a transparent coating.
[0122] Comparative Example 3
[0123] (1) Place the glass slide in water and use an ultrasonic cleaner to sonicate for 15 minutes, then place the substrate in ethanol and use an ultrasonic cleaner to sonicate for 15 minutes to obtain a substrate with a clean surface.
[0124] (2) Add 0.4 g of photoinitiator 184-L and 20 g of ethanol to 10 g of organic-inorganic hybrid silicone resin, and stir evenly to obtain a mixed coating, wherein the organic-inorganic hybrid silicone resin is the silicone resin in Example 3.
[0125] (3) spraying the mixed coating onto a cleaned glass slide at a pressure of 0.25 MPa;
[0126] (4) The glass slide sprayed with the mixed coating was placed under a UV-LED lamp and irradiated with ultraviolet light for 90 seconds to obtain a transparent coating.
[0127] Comparative Example 4
[0128] (1) Place the glass slide in water and use an ultrasonic cleaner to sonicate for 15 minutes, then place the substrate in ethanol and use an ultrasonic cleaner to sonicate for 15 minutes to obtain a substrate with a clean surface.
[0129] (2) Add 0.4 g of photoinitiator 184-L and 20 g of ethanol to 10 g of organic-inorganic hybrid silicone resin, and stir evenly to obtain a mixed coating, wherein the organic-inorganic hybrid silicone resin is the silicone resin in Example 4.
[0130] (3) spraying the mixed coating onto a cleaned glass slide at a pressure of 0.25 MPa;
[0131] (4) The glass slide sprayed with the mixed coating was placed under a UV-LED lamp and irradiated with ultraviolet light for 90 seconds to obtain a transparent coating.
[0132] Performance Testing:
[0133] (1) Contact angle test: The contact angles of the coatings prepared in Examples 1 to 6 and Comparative Examples 1 to 4 were measured using a standard contact angle meter. The results are shown in Table 1.
[0134] (2) Anti-fingerprint performance test: The artificial fingerprint liquid is composed of 95% artificial sweat and 5% artificial sebum. The artificial sweat is prepared by mixing 3mL / L of lactic acid, 5mL / L of acetic acid, 10g / L of sodium chloride, 10g / L of sodium hydrogen phosphate and deionized water, and the artificial sebum is composed of oleic acid (2%), stearic acid (2%) and squalene (1%). After the artificial sweat and artificial sebum are mixed, a small amount of non-ionic surfactant (Triton X100, added in an amount of 2μL / g of the mixture) is added to overcome the natural immiscibility between sweat and sebum. First, clean the finger with alcohol, immerse the finger in the artificial fingerprint liquid, and then touch the coating surface to form a fingerprint. Then wipe it with a paper towel at a speed of 3cm / s under a load of 500g, and record the number of wipes that can make the fingerprint disappear. The results are shown in Table 1.
[0135] (3) Pencil hardness test: According to the requirements of ASTM D3363, the hardness of the coating is measured using a series of pencils with hardness ranging from 6B to 9H.
[0136] (4) Wear resistance test: Steel wool was used to rub the sample 500 times at a speed of 3 cm / s under a load of 500 g, and the water contact angle of the rubbed sample was measured.
[0137] (5) Transmittance test: The transmittance of different coatings was measured using a UV-visible spectrophotometer, with the transmittance at 550 nm being the standard. The results are shown in Table 1.
[0138] Table 1 Water contact angle, pencil hardness, anti-fingerprint performance, wear resistance and transmittance of the coatings prepared in Examples 1 to 6 and Comparative Examples 1 to 4.
[0139]
[0140]
[0141] It can be seen from the above examples and the experimental data in Table 1 that the present invention provides an organic-inorganic hybrid fluorine-free anti-fingerprint transparent coating and its preparation method and application. The organic-inorganic hybrid coating prepared by the present invention is a transparent coating with low surface energy and high hardness. The coating can be quickly photocured to reach a surface dry state, and has high production efficiency; the coating does not contain fluorine and is environmentally friendly. The prepared coating has a water contact angle greater than 95° and a light transmittance greater than 85%. Fingerprints can be removed by wiping with a napkin 3 times or less, and has excellent wear resistance.
[0142] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing an organic-inorganic hybrid fluorine-free anti-fingerprint transparent coating, characterized in that: The following steps are involved: 1) mixing an organic-inorganic hybrid silicone resin, a tung oil derivative, a photoinitiator and an organic solvent to obtain a mixed coating; 2) The mixed coating is coated on a substrate and cured by ultraviolet light to obtain an organic-inorganic hybrid fluorine-free anti-fingerprint transparent coating.
2. The preparation method according to claim 1, characterized in that: The preparation method of the organic-inorganic hybrid silicone resin comprises the following steps: Mixing siloxane, tetraethyl silicate and a silane coupling agent in an acidic solvent for hydrolysis to obtain an organic-inorganic hybrid silicone resin; The molar ratio of the siloxane, tetraethyl silicate and silane coupling agent is 1:0.2-9:0.2-9.
3. The preparation method according to claim 2, characterized in that: The siloxane comprises one or more of trimethylchlorosiloxane, tetramethyldivinyldisiloxane, vinylpentamethyldisiloxane, trimethylmethoxysilane, trimethylethoxysilane, hexamethyldisiloxane, dimethyldimethoxysilane and dimethyldiethoxysilane; The silane coupling agent comprises one or more of γ-methacryloxypropyl trimethoxysilane, γ-methacryloxypropyl triethoxysilane, γ-mercaptopropyl trimethoxysilane, γ-mercaptopropyl triethoxysilane, γ-glycidyloxypropyl trimethoxysilane, γ-glycidyloxypropyl triethoxysilane, γ-aminopropyl triethoxysilane, γ-aminopropyl trimethoxysilane, vinyl trimethoxysilane, vinyl triethoxysilane, phenyl trimethoxysilane, phenyl triethoxysilane, dodecyl trimethoxysilane, dodecyl triethoxysilane, hexadecyl trimethoxysilane, hexadecyl triethoxysilane, methyl triethoxysilane and methyl trimethoxysilane; The acid in the acidic solvent comprises one or more of toluenesulfonic acid, oxalic acid, hydrochloric acid and acetic acid; the solvent in the acidic solvent comprises at least two of toluene, methanol, ethanol, ethylene glycol, glycerol, ethylene glycol methyl ether, ethylene glycol butyl ether, propylene glycol methyl ether, chloroform, tetrahydrofuran, butyl acetate, dimethyl sulfoxide, isopropanol and water, and the amount of the acidic solvent is 10-60% of the total mass of siloxane, tetraethyl silicate and silane coupling agent.
4. The preparation method according to claim 2 or 3, characterized in that: The hydrolysis temperature is 25-90° C., and the hydrolysis time is 6-24 hours.
5. The preparation method according to claim 1, characterized in that: The preparation method of the tung oil derivative comprises the following steps: Tung oil anhydride, acrylate monomer and polymerization inhibitor are mixed, and reacted under heating and the action of a catalyst to obtain a tung oil derivative; The molar ratio of tung oil anhydride to acrylate monomer is 1:5-7, the content of the inhibitor is 0.5-5% of the total mass of tung oil anhydride and acrylate monomer, and the mass of the catalyst is 0.1-2% of the total mass of tung oil anhydride and acrylate monomer; The mass of the tung oil derivative is 1-50% of the total mass of the organic-inorganic hybrid silicone resin and the tung oil derivative.
6. The preparation method according to claim 5, characterized in that: The acrylate monomer comprises one or more of hydroxyethyl methacrylate, 2-hydroxyethyl acrylate, glycidyl methacrylate, 2-ethoxyethyl acrylate, 2-cyanoacrylate, β-hydroxypropyl acrylate, β-hydroxypropyl methacrylate, dipentaerythritol pentaacrylate and pentaerythritol triacrylate; the polymerization inhibitor comprises one or more of hydroquinone, p-hydroxyanisole and methylhydroquinone; the catalyst comprises p-toluenesulfonic acid and / or N,N-dimethylethanolamine; The reaction temperature is 60-100° C., and the reaction time is 4-12 hours.
7. The preparation method according to claim 1, 2 or 6, characterized in that: The photoinitiator comprises one or more of photoinitiator 250, photoinitiator 6992, photoinitiator BDK, photoinitiator 369, photoinitiator MBF, photoinitiator PBZ, photoinitiator EDB, photoinitiator 379, photoinitiator 784, photoinitiator 2959, photoinitiator 184-L, photoinitiator TPO, photoinitiator TPO-L and photoinitiator 1173; the mass of the photoinitiator is 1 to 5% of the total mass of the organic-inorganic hybrid silicone resin and the tung oil derivative.
8. The preparation method according to claim 7, characterized in that: The organic solvent comprises one or more of acetone, tetrahydrofuran, ethanol, methanol, ethyl acetate, n-butyl acetate, chloroform, dichloromethane, dimethyl sulfoxide, propylene glycol methyl ether, ethylene glycol butyl ether, n-pentane and toluene; the mass of the organic solvent is 1 to 10 times the total mass of the organic-inorganic hybrid silicone resin and the tung oil derivative.
9. The organic-inorganic hybrid fluorine-free anti-fingerprint transparent coating prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the organic-inorganic hybrid fluorine-free anti-fingerprint transparent coating according to claim 9 in anti-fingerprint self-cleaning wear-resistant materials.
Citation Information
Patent Citations
Preparation method of highly-hydrophobic fluorocarbon coating for photovoltaic component back plate
CN104530852A
Preparation method of light-cured resin containing silicon nano gel for 3D printing and application of light-cured resin
CN106146754A
Anti-corrosion and anti-icing self-cleaning super-hydrophobic coating as well as preparation method and application thereof
CN113372803A
Preparation methods and applications of high-hardness organic-inorganic hybrid UV-curable coatings
CN102295881A
Vegetable oil modified fluoride-free anti-fingerprint transparent coating material as well as preparation method and application thereof
CN117986998A
Cited By
Organic-inorganic hybrid material and preparation method thereof, transparent coating and preparation method thereof, and flexible electronic equipment
CN122325755A